2021
DOI: 10.1021/acs.est.1c05908
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Catalytic Purification of Auto-Exhaust Carbon Particles via the Fe2O3{113} Facet-dependent Effect in Pt/Fe2O3 Catalysts

Abstract: The purification efficiency of auto-exhaust carbon particles in the catalytic aftertreatment system of vehicle exhaust is strongly dependent on the interface nanostructure between the noble metal component and oxide supports. Herein, we have elaborately synthesized the catalysts (Pt/Fe2O3-R) of Pt nanoparticles decorated on the hexagonal bipyramid α-Fe2O3 nanocrystals with co-exposed twelve {113} and six {104} facets. The area ratios (R) of co-exposed {113} to {104} facets in α-Fe2O3 nanocrystals were adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…The peak position of Fe 2p 3/2 was fitted into two peaks: the Fe 2+ valence state was characterized by Fe 2p 3/2 peak (BE = 710.9 eV), whereas the Fe 2p 3/2 signal at 714.1 eV was indicative of the presence of surface Fe 3+ . One peak located at around 718.4 eV is assigned to the satellite peak of Fe 2p 3/2 , which can prove the formation of Fe 3+ species at the surface of the catalysts . According to calculations, the ratio of Fe 3+ /Fe is 60.5% .…”
Section: Resultsmentioning
confidence: 89%
“…The peak position of Fe 2p 3/2 was fitted into two peaks: the Fe 2+ valence state was characterized by Fe 2p 3/2 peak (BE = 710.9 eV), whereas the Fe 2p 3/2 signal at 714.1 eV was indicative of the presence of surface Fe 3+ . One peak located at around 718.4 eV is assigned to the satellite peak of Fe 2p 3/2 , which can prove the formation of Fe 3+ species at the surface of the catalysts . According to calculations, the ratio of Fe 3+ /Fe is 60.5% .…”
Section: Resultsmentioning
confidence: 89%
“…The reaction mechanism of Nox-assisted soot oxidation has also been determined. Li 33 37 used this method to study the electrontransfer mechanism during the oxidation of soot. Wang 38 et al used the DFT method to prove that oxygen vacancies and alkali metals can promote the soot combustion activity of CeO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Deng et al reported that the Fe 2 O 3 {113} facet interaction increased the density of the active oxygen species, further boosting the activation of O 2 and NO. 10 Similarly, hollow α-Fe 2 O 3 octadecahedra enclosed by the {113} and {104} facets were conducive to the generation of O-vacancy and surface OH species, resulting in high activity and stability of HCHO. 11 However, there have been a few studies and efforts in developing facet-enclosed α-Fe 2 O 3 -based HCHO gas-sensing devices at room temperature.…”
Section: Introductionmentioning
confidence: 99%